Lived experiences of Turkish community pharmacists toward person-centric care: a qualitative analysis - Elif Ulutas Deniz; Muhammad Kamran Rasheed; Rumeysa Eren; Hatice Gözeler (Taylor & Francis Group, 2024)
Background: In Turkey, the SMART pharmacist program was launched to enable community pharmacists to deliver patient-centric care services. However, how far this programme has achieved success and what are the challenges faced by the programme need to be evaluated. Objective: This study aimed to explore the experiences of community pharmacists in providing person-centric care services in pharmacies and provide recommendations for improved care effectiveness. Methods: A phenomenological approach was adopted in this study. To conduct qualitative interviews, a semi-structured interview guide was devised to gather insights from the pharmacists. The interviews were coded verbatim. Subsequently, various themes and sub-themes were developed based on the aim and objectives of the study. A total of 14 pharmacists engaged in semi-structured interviews conducted between May and August 2023. Results: Two main themes emerged from the data: challenges in person-centric care and recommendations to improve person-centric care. Barriers were subdivided into patient-related challenges and personal challenges. Recommendations consisted of pharmacists' professional tasks and recommendations. Conclusion: The findings of this study, suggest that the concerned healthcare authorities should re-evaluate the 'SMART pharmacist' program in Turkey and address professional and personal challenges faced by community pharmacists in delivering effective person-centric care. Pharmacists recommend patient follow-up (follow-ups), providing a counselling environment, collaboration with physicians, expansion of pharmacy services.